2017
DOI: 10.18203/2320-1770.ijrcog20172632
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcome in post term pregnancy

Abstract: Background:The term delivery is defined as that occurring between 259 and 294 days of pregnancy from the last menstrual period. If the pregnancy exceeds this period, it is called as post term pregnancy. Our center is in rural area where most of the patients are unbooked or even booked patients are also loss of follow up. So, this study was done to know the incidence of prolonged pregnancy and maternal and fetal outcome in case of prolonged pregnancy in our rural population. Methods: This study was a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
2
2
Order By: Relevance
“…It is consistent with the study which found that 15.38% of neonates were admitted to NICU and 3.84% infants were having>4 kg birth weight. 8 Similar results were found in study which was done in Indira Gandhi Institute of Medical Sciences, Patna which showed that out of 100 postdates pregnancies, 11% of neonates had macrosomia whereas 25% of neonates were admitted to NICU. 13 In the present study, no perinatal mortality was found.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is consistent with the study which found that 15.38% of neonates were admitted to NICU and 3.84% infants were having>4 kg birth weight. 8 Similar results were found in study which was done in Indira Gandhi Institute of Medical Sciences, Patna which showed that out of 100 postdates pregnancies, 11% of neonates had macrosomia whereas 25% of neonates were admitted to NICU. 13 In the present study, no perinatal mortality was found.…”
Section: Discussionsupporting
confidence: 82%
“…3 Another study done in Nagpur, India showed that majority of the mothers (69.8%) were also in 40 -41 weeks of gestation. 8 In contrast to the study's finding, a study conducted in Ahemdabad, India, revealed that more than half of the mothers 54.76 % were more than 41 weeks of gestation. 5 In this study, maximum cases (69.4%) delivered normally, whereas caesarean section were performed in 30.6% cases.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In this retrospective study, the incidence of post-term pregnancy is 1.25%, which is much less than reported by other studies (8.3%) by Ingemarsson et al 5 9 In a study by Nimbargi et al the caesarean section rate was 61.3%. 10 The rate of surgical intervention is increased in post term pregnancies because of meconium staining of amniotic fluid, non-progress of labour, intrapartum foetal hypoxia and oligohydramnios.…”
Section: Discussioncontrasting
confidence: 55%
“…In present study 72% infants were having 2.5 to 3.9 kg birth weight which was less than the study conducted by Verma et al which showed 87% infants of birth weight 2.5 to 3.9 kg. 12 In the present study, maternal outcome was comparable between the two groups. Out of 168 patients, 15 (8.9%) had PPH in which 6 patients were full term and 9 were late term, 8 (4.8%) had chorioamnionitis in which 5 were full term and 3 were late term and 5 (3%) had uterine hyperstimulation in which 1 was full term and 4 were late term pregnancies (p=0.305).…”
Section: Discussionsupporting
confidence: 47%